(untitled) (Bonn, Germany, 1986)
This book introduces about Papers on Japanese economic history, Papers on contemporary Japanese economics.
Keywords: Nhật Bản,Japan; Điều kiện kinh tế,Hội nghị,Economic conditions,Congresses